South Africa’s Non-Aligned Stance on the Russia-Ukraine War: Implications on South Africa’s Economic Trade Relations - Thoriso Ntlailane; Costa Hofisi (E-Journal of Humanities, Arts and Social Sciences)
The foreign policy of non-alignment adopted by various states during the Russia-Ukraine war has been interpreted differently in the landscape of global politics. One perspective views non-alignment as tacit support for Russia’s invasion of Ukraine, while the other sees it as a way for countries to protect their national interests. The study explored the non-alignment stance of the South African government on the Russia-Ukraine war and its effect on the economy of the state. It observed the trade relations that South Africa has with states that condemned the acts of Russia’s invasion of Ukraine. Not only that but also, the trade relations of South Africa with states that used the non-alignment foreign policy in the Russia-Ukraine war. The response of South Africa’s markets to the non-alignment stance on the Russia-Ukraine war was also examined. The paper made use of the qualitative research method and secondary data. Furthermore, the study employed document analysis as a research technique. The study findings show that the non-alignment stance of South Africa had minimal and short-term implications for the country. However, the position of non-alignment by the South African government has been perceived to be controversial and supporting the actions of Russia in the war. The paper concluded that South Africa’s stance has minimal effect on the state’s economy. The study contributes to knowledge by demonstrating the implications of South Africa’s Non-Aligned Stance On The Russia-Ukraine War on South Africa’s Economic Trade Relations.